Weibull Regression Model on Hospitalization Time Data of COVID-19 Patients at Abdul Wahab Sjahranie Hospital Samarinda - Khairunnisa, Siti Fatimah; Suyitno, Suyitno; Mahmuda, Siti (Jurnal Matematika, Statistika dan Komputasi, 2023)
The Weibull regression model is a Weibull distribution that is directly influenced by covariates. The Weibull regression model discussed in this study was the Weibull survival and the Weibull hazard regression model. The Weibull regression model in this study was applied to the hospitalization time data of COVID-19 patients from May to September 2021 at the RSUD Abdul Wahab Sjahranie Samarinda. The event of the study is recovery of patient. This study aims to obtain Weibull survival and hazard regression model to the hospitalization time data of Covid-19 patients, to obtain the factors that affect the chance of not recovering (survive) and the recovery rate of Covid-19 patients, and also to interpret Weibull survival and hazard regression models based on the obtained model. In this study, the Maximum Likelihood Estimation (MLE) was used as the parameter estimation method. The closed form of the Maximum Likelihood (ML) estimator cannot be found analytically, and the approximation of ML estimator was found using Newton-Raphson iterative method. Based on the test results, the factors that influence the chance of not recovering and the recovery rate of COVID-19 patients were comorbidities history. The chance of not not recovering (survive) for patients who have a history of comorbidities is greater than the chance of not recovering (survive) for patients who have no history of comorbidities. The recovery rate for COVID-19 patients who have a history of comorbidities is 0,5358 times the recovery rate for patients without a history of comorbidities.